The Effect of Changes in Thyroid Hormone Levels on Learning and Memory in Middle Aged Rats - Ercan BABUR; Rabia KURT TOKPINAR; Nurcan DURSUN; Burak TAN; Cem SÜER (Namık Kemal Tıp Dergisi, 2023)

(untitled)
Aim: The increase in the frequency of thyroid diseases in old age makes it necessary to reveal the relationship between aging and irregularities in thyroid hormone levels. In the present study, the effects of experimental hypothyroidism and thyrotoxicosis induced in middle aged rats on spatial learning and memory performance were investigated. Materials and Methods: In this study, 45 Wistar albino 12-month-old rats weighing 400-450 g were used. The rats were divided into three groups according to thyroid hormone levels; euthyroid (n=16), hyperthyroid (n=16) and hypothyroid (n=13). Thyrotoxicosis was induced by intraperitoneal (i.p.). administration of L-thyroxine at a dose of 0.2 mg/kg/day. Hypothyroid state was induced by daily administration of 0.05% 6-n-propyl-thiouracil (PTU) in the drinking water of rats. Spatial memory and learning performance of rats were evaluated by Morris water maze test. Thyroid hormone levels were determined with a commercial ELISA kit. Results: One-way ANOVA test revealed that the mean distance to the platform (p<0.05), escape time (p<0.01), swimming speed (p<0.001) and distance traveled (p<0.05) values of the rats showed significant differences between the groups. According to these results; learning performance of the hypothyroidism group decreased compared to the control group, while learning and memory performance of the thyrotoxicosis group did not differ from the control group. Conclusion: Hypothyroidism during aging has a negative effect on learning and memory performance compared to thyrotoxicosis. Revealing the changes in thyroid hormone metabolism in middle aged and determining the daily requirement will provide a different perspective on aging-related dementia-type diseases.